ANALISA KONSEP KHALLED ABOU EL FADL, ABDUL KARIM SOROUSH DAN MUHAMMAD ABID AL-JABIRI DALAM PENGKAJIAN FILSAFAT HUKUM DAN EKONOMI ISLAM - Ash-Shiddiqy, Muhammad (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
This study contains the concepts of thought of Khaled M. Abou El Fadl, Abdul Karim Soroush and Muhammad Abid Al Jabiri in the study of Islamic legal and economic philosophy. In this paper, it is clearly explained how important it is to examine the thoughts of these three figures in the study of the philosophy of Islamic sciences. Philosophy of Islamic sciences is very beneficial and motivates us to always strive to study religious science with all the abilities it has in order to become a complete human being and continuously improve ourselves. Finally, it is very important for every Muslim to study the philosophy of Islamic science which can expand his religious knowledge and have more pluralist and democratic thoughts in religious life.